Co-delivery of deferoxamine and hydroxysafflor yellow A to accelerate diabetic wound healing via enhanced angiogenesis. (1st January 2018) - Gao, Si-Qian; Chang, Chen; Li, Jun-Jun; Li, Ying; Niu, Xiao-Qian; Zhang, Dan-Ping; Li, Long-Jian; Gao, Jian-Qing
Abstract: Nonhealing chronic wounds on foot induced by diabetes is a complicated pathologic process. They are mainly caused by impaired neovascularization, neuropathy, and excessive inflammation. A strategy, which can accelerate the vessel network formation as well as inhibit inflammatory response at the same time, makes it possible for effective diabetic ulcers treatment. Co-delivery of multiple drugs with complementary bioactivity offers a strategy to properly treat diabetic wound. We previously demonstrated that hydroxysafflor yellow A (HSYA) could accelerate diabetic wound healing through promoting angiogenesis and reducing inflammatory response. In order to further enhance blood vessel formation, a pro-angiogenic molecular called deferoxamine (DFO) was topically co-administrated with HSYA. The in vitro results showed that the combination of DFO and HSYA exerted synergistic effect on enhancing angiogenesis by upregulation of hypoxia inducible factor-1 alpha (HIF-1α) expression. The interpenetrating polymer networks hydrogels, characterized by good breathability and water absorption, were designed for co-loading of DFO and HSYA aiming to recruit angiogenesis relative cells and upgrade wound healing in vivo . Both DFO and HSYA in hydrogel have achieved sustained release. The in vivo studies indicated that HSYA/DFO hydrogel could accelerate diabetic wound healing. With a high expression of Hif-1α which is similar to that of normal tissue. The noninvasive US/PA imaging revealed that the wound could be recovered completely with abundant blood perfusion in dermis after given HSYA/DFO hydrogel for 28 days. In conclusion, combination of pro-angiogenic small molecule DFO and HSYA in hydrogel provides a promising strategy to productively promote diabetic wound healing as well as better the repair quality. Graphical Abstract: